Rencana Strategi PT Nusantara Agri Teknologi : Transformasi Inovasi dalam Pengolahan Sumber Daya Alam - Dwi Astuti; Ardiansyah Ardiansyah (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
Digital transformation has become an urgent necessity in the effort to modernize the agricultural sector in Indonesia. This sector faces numerous challenges, including low productivity, climate change, and limited land availability. This study examines the digital transformation strategies implemented by PT Nusantara Agri Teknologi (NAT), an agritech startup that leverages Internet of Things (IoT), artificial intelligence (AI), and data analytics to develop precision agriculture. Using a qualitative case study approach involving interviews, observations, and document analysis, the research evaluates NAT’s corporate, operational, and social strategies. The findings reveal that digital technology adoption can increase partner farmers’ crop yields by up to 27%, while reducing input usage and boosting their income. However, a major challenge remains: low digital literacy and limited human resources (HR). To address these issues, NAT has implemented digital education programs and formed partnerships with farmer groups and universities. The study concludes that the success of digital transformation depends not only on technological innovation but also on social empowerment and the active, sustained participation of farming communities.